Stres Kerja, Kompetensi, Kompensasi dan Pengaruhnya Terhadap Kinerja Karyawan dengan Motivasi Sebagai Variabel Intervening - Vera Subchanifa, Dian Pujiatama; S, Surepno; Istiqomah, Nugraheni (IAIN Kudus, 2020)
This study aims to obtain empirical evidence about the effect of work stress, competence, and compensation on employee performance with motivation as an intervening variable at KSPPS Fastabiq Khoiro Ummah Pati. The research method uses quantitative methods with the research sample of employees at KSPPS Fastabiq Khoiro Ummah Pati who have worked. minimum one year, amounting to 76 employees. The results showed that the work stress variable harmed employee performance. While the competency and compensation, variables have a positive and significant effect on employee performance. Job stress and competency variables do not affect employee performance which is mediated by work motivation. While the compensation variable affects employee performance mediated by work motivation.